Side Effects of COVID-19 Vaccines Primer Doses: Experience of Saudi Healthcare Workers Participating in CoVaST-SA - Riad, Abanoub; Alsaad, Safa S; Almurikhi, Ali A; Alzahrani, Fayez A; Alghamdi, Ali M; Alzaid, Esra H; Klugar, Miloslav (Vaccines, 2022)
BACKGROUND: Side effects emerging after COVID-19 vaccines may adversely impact public confidence in vaccines. Therefore, this study was designed to explore the short-term side effects of COVID-19 vaccines as a part of the COVID-19 Vaccines Safety Tracking (CoVaST) study. METHODS: A cross-sectional survey-based study was carried out to collect data from healthcare workers (HCWs) in Saudi Arabia. The study was initiated between June and December 2021. A validated questionnaire was used in this study consisting of four categories, including demographic characteristics and medical anamnesis of the participants, COVID-19-associated anamnesis, and side effects of vaccine uptake. RESULTS: The study included 1039 participants, of which 70.2% were females, and their median age was 34. About 82.9% and 52.3% of the participants reported a minimum of both one local and systemic side effect, respectively. Females, young participants (≤34 years old), and non-obese participants had more potential to disclose post-vaccination side effects than their counterparts. Heterologous schedules and viral vector-based vaccines were linked with a greater rate of systemic side effects, whereas homologous vaccination schedules and mRNA-based vaccines were linked with a greater rate of local side effects. CONCLUSION: Future studies on COVID-19 vaccines should focus on the role of BMI, previous infection, and vaccination schedule in terms of vaccine safety and reactogenicity.